Knowledge, attitude, and practice regarding COVID-19 pandemic among medical students of Ernakulam, India - Kalliath, Jacob Davies; Kizhatil, Anuradha; Rose, Brilly M; Kuncheria, Ann Mary; John, Alexander (Journal of Ideas in Health, 2021)
Background: COVID – 19 infection is a serious pandemic the world is now facing. This study aimed to assess the knowledge, attitude, and practice regarding COVID-19 infection among medical students at a private medical college in central Kerala. Methods: A cross-sectional web-based study was conducted during April-May 2020 in a private medical college in Ernakulam District using the Universal sampling technique. The study tool was a semi-structured validated questionnaire containing sociodemographic details and questions on knowledge, attitude, and practice (KAP) regarding COVID-19 infection. Data were analyzed using SPSS version 20 software. Results: A total of 288 students were included in the study, with a mean age of 21±1.4. The male-to-female ratio was 2.75:1. Medical students showed adequate knowledge (81.6%), attitude (91.3%), and practice (84.7%) towards the COVID-19 pandemic, respectively. The main symptoms of COVID-19 infection were known to at least 83% of the participants. The majority (85.4%) were aware that there is no specific treatment for COVID-19 infection and 90% were aware of the main modes of the disease transmission. The majority (99%) of the medical students believed that COVID-19 infection could be prevented through social distancing, wearing masks, and the practice of self-hygiene. About 75.6% believed that government measures for prevention are adequate. Steam inhalation, saline gargling, and consumption of vitamin C-rich foodstuffs were the main specific measures adopted. Older age and female gender were found to be associated with better knowledge. Conclusion: Adequate KAP levels among medical students in this study are attributable to the current lockdown and the strict government measures to contain the infection.